Determinants of Myocardial Lactate Production During Acetylcholine Provocation Test in Patients With Coronary Spasm. Issue 12 (10th December 2015) - Kaikita, Koichi; Ishii, Masanobu; Sato, Koji; Nakayama, Masafumi; Arima, Yuichiro; Tanaka, Tomoko; Sugamura, Koichi; Sakamoto, Kenji; Izumiya, Yasuhiro; Yamamoto, Eiichiro; Tsujita, Kenichi; Yamamuro, Megumi; et al.
Abstract : Background: Myocardial lactate production in the coronary circulation during acetylcholine (ACh)‐provocation test (abbreviated as lactate production) provides supporting evidence for coronary spasm–induced myocardial ischemia. The purpose of this study was to examine the clinical features, predictive factors, and prognosis of patients with coronary vasospastic angina (VSA) and lactate production. Methods and Results: We examined all 712 patients who underwent both myocardial lactate measurement during ACh‐provocation test in the left coronary artery and genetic screening test of a –786T/C polymorphism in the 5′‐flanking region of the endothelial nitric oxide synthase ( eNOS ) gene between January 1991 and December 2010. Lactate production was observed in 252 of the 712 patients and in 219 of 356 VSA patients diagnosed by ACh‐provocation test. Compared with lactate production–negative VSA patients, the lactate production–positive counterparts were more likely to be nonsmoker female diabetics with –786T/C eNOS polymorphism (61% vs 31%, P <0.001, 62% vs 34%, P <0.001, 24% vs 14%, P =0.016, and 25% vs 15%, P =0.018, respectively). Multivariable logistic regression analysis identified female sex, diabetes mellitus, and –786T/C eNOS polymorphism to correlate with lactate production (odds ratio 3.51, 95% CI 2.16 to 5.70, P <0.001; odds ratio 2.53, 95% CI 1.38 to 4.65, P =0.003; and odds ratio 1.85, 95% CI 1.02 to 3.35, P =0.044, respectively). Kaplan–Meier survival curve showed no difference in 5‐year survival rate free from major adverse cardiac events between lactate production–positive and –negative VSA patients ( P =0.319). Conclusions: The results indicated that female sex, diabetes, and mutation in –786T/C eNOS gene correlate with ACh‐provoked myocardial ischemia in patients with coronary spasm.